Model Penjelasan Intensi Cerai Perempuan Muslim di Sulawesi Selatan - Asniar Khumas; Johana E Prawitasari; Sofia Retnowati; Rahmat Hidayat (Faculty of Psychology, Universitas Gadjah Mada, 2015)
The study tested the explanatory model of intentions for divorce based on the theory of social exchange, theory of planned behavior by Ajzen and model of dissolution by Amato and Rogers. The 197 subjects participating in this study were wives who had filed for divorce at the religious courts in several districts and cities in South Sulawesi. The measuring tools of the study were divorce intention scale and marital relationship scale developed by the researcher based on theoretical constructs of each tested factor. The theoretical model developed was tested with analysis of Structural Equation Models (SEM). The results of the study revealed that the intentions of divorce could be explained by the strong effects of negative relationships such as domestic violence, infidelity and irresponsibility. It was also found that there were weak barriers to divorce and post-divorce expectation of a better life with new partner who could love them more. Indirect factor that contributed to divorce intention was level of education. These findings confirmed the explanatory models of divorce intention based on social exchange theory, planned behavior theory, and the suggested Amato and Rogers’ divorce models.